(untitled) (World Bulletin of Public Health, 2025)
The article presents the results of periodontal microcirculation assessment during the immobilization period in patients with alveolar process fractures of the jaws. During immobilization, along with the main treatment, attention should be paid to implementing a set of measures that improve microcirculation indicators and prevent the progression of inflammatory-destructive changes in the periodontal tissues of patients with jaw alveolar process fractures